Estudio de diversas preparaciones y diluciones de biol en la productividad del cultivo de maíz (Zea mays L.). - Vera Vera, Luis Arturo (2011)
This study aimed to generate information about the different preparations of biol and its benefit on the productivity of maize (Zea mays U. The factors studied were: type of biological (biol common tactic acid bacteria biol, blot with chelates, biol total) and dilution rates (5%, 10%, 15%). Using a design of a randomized complete block (DBCA) under bivariate additive (MB +1) with three blocks. For statistical analysis, variables were subjected to Tukey means test at 0.05% chance of error and the economic analysis was that estans-ise; by CIMMYT, the variables evaluated were: plant height and stem diameter at 30, 45, 60 days after sowing, plant height at harvest, diameter, length and number of rows per ear, weight of 100 grains, yield per plot and per hectare; tiese to be evaluated statistically significant differences were found for both treatments to the factors under study. But numerically the treatments were more favorable for the variables studied both morphologically and in production were the chemical control (TO) the total biol 15% dilution (B4D3) and common biol 15% dilution (BI D3). Economically biol treatment with lactic add bacteria to 5% dilution (132D1) gave the best return rate with 748% marginal.